2001
DOI: 10.1023/a:1008304128577
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycemic load and colorectal cancer risk

Abstract: The positive associations of glycemic index and load with colorectal cancer suggest a detrimental role of refined carbohydrates in the etiology of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1
8

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(116 citation statements)
references
References 27 publications
4
100
1
8
Order By: Relevance
“…The results were adjusted for sociodemographic factors, physical activity, number of daily meals, and intakes of fiber, alcohol and energy. ORs were especially elevated for cancer of the colon (1.9 for GI and 2.0 for GL; Franceschi et al, 2001). These data suggest the more refined the carbohydrates in the habitual diet, the greater the risk for cancer of the colorectum.…”
Section: Colorectal Cancermentioning
confidence: 85%
See 1 more Smart Citation
“…The results were adjusted for sociodemographic factors, physical activity, number of daily meals, and intakes of fiber, alcohol and energy. ORs were especially elevated for cancer of the colon (1.9 for GI and 2.0 for GL; Franceschi et al, 2001). These data suggest the more refined the carbohydrates in the habitual diet, the greater the risk for cancer of the colorectum.…”
Section: Colorectal Cancermentioning
confidence: 85%
“…Three epidemiological studies have looked at this and found direct associations for colorectal and breast cancer (Slattery et al, 1997;Franceschi et al, 2001;Augustin et al, 2001).…”
Section: Glycemic Index and Cancermentioning
confidence: 99%
“…The case control studies have found consistent increased risk of a high glycemic load with gastric [12], upper aero digestive tract [13], endometrial [14], ovarian [15], colon or colorectal cancers [16,17]. The prospective studies' results have been mixed.…”
Section: Reviewmentioning
confidence: 99%
“…An increased risk of colorectal cancer emerged for high GI (OR 5 1?7) and GL (OR 5 1?8) after allowance for several covariates, including dietary fibres (33) . The OR were higher for colon than rectal cancer.…”
Section: Glycaemic Index and Glycaemic Loadmentioning
confidence: 99%